Anxiety associated with diagnostic uncertainty in early pregnancy. (27th June 2017) - Richardson, A.; Raine‐Fenning, N.; Deb, S.; Campbell, B.; Vedhara, K.
ABSTRACT: Objectives: To determine anxiety levels of women presenting to an early pregnancy assessment unit (EPAU) with abdominal pain and/or vaginal bleeding and to assess how these levels change over time and according to ultrasonographic diagnosis. Methods: We undertook a prospective cohort study in an EPAU in a large UK teaching hospital. Women with abdominal pain and/or vaginal bleeding in early pregnancy (< 12 weeks' gestation) presenting for the first time were eligible for inclusion in the study. State anxiety levels were assessed using the standardized short form of Spielberger's state–trait anxiety inventory (STAI) on three occasions (before, immediately after and 48–72 hours after an ultrasound scan). Scores were correlated with ultrasonographic diagnosis. The diagnosis was either certain or uncertain. Certain diagnoses were either positive, i.e. a viable intrauterine pregnancy (IUP), or negative, i.e. a non‐viable IUP or ectopic pregnancy. Uncertain diagnoses included pregnancy of unknown location and pregnancy of uncertain viability. Statistical analysis involved mixed ANOVAs and the post‐hoc Tukey–Kramer test. Results: A total of 160 women were included in the study. Anxiety levels decreased over time for women with a certain diagnosis ( n = 128), even when negative ( n = 64), and increased over time for women with an uncertain diagnosis ( n = 32). Before the ultrasound examination, anxiety levels were high (STAI value, 21.96 ± 1.11) and there was no significant difference between the five groups. Immediately after the ultrasound examination, anxiety levels were lower in the viable IUP group ( n = 64; 7.75 ± 1.13) than in any other group. The difference between the five groups was significant ( P < 0.005). After 48–72 hours, women with a certain diagnosis had significantly lower anxiety levels than had those with an uncertain diagnosis (10.77 ± 4.30 vs 22.94 ± 1.65; P < 0.005). Conclusions: The experience of abdominal pain and/or vaginal bleeding in early pregnancy is highly anxiogenic. Following an ultrasound examination, the certainty of the diagnosis affects anxiety levels more than does the positive or negative connotations associated with the diagnosis per se. Healthcare providers should be aware of this when communicating uncertain diagnoses. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.